Mass Cytometry Reveals a Sustained Reduction in CD16+ Natural Killer Cells Following Chemotherapy in Colorectal Cancer Patients - Shinko, Diana; McGuire, Helen M.; Diakos, Connie I.; Pavlakis, Nick; Clarke, Stephen J.; Byrne, Scott N.; Charles, Kellie A. (Frontiers in Immunology, 2019)
The immune system and inflammation plays a significant role in tumour immune evasion enhancing disease progression and reducing survival in colorectal cancer. Patients with advanced stages of colorectal cancer will all undergo treatment with cytotoxic chemotherapy which may alter the complexity of immune cell populations. This study used mass cytometry to comprehensively investigate the circulating immune cell profile of advanced CRC patients following acute and chronic doses of standard cytotoxic chemotherapy and analysed 7 major immune cell populations and over 20 subpopulations. Unsupervised clustering analysis of the mass cytometry data revealed a decrease in NK cells following one cycle of cytotoxic chemotherapy. Investigation into the NK sub-population revealed a decline in the CD56dim CD16+ NK cell population following acute and chronic chemotherapy treatment. Further analysis into the frequency of the NK cell sub-populations during the long-term chemotherapy treatment revealed a shift in the sub-populations, with a decrease in the mature, cytotoxic CD56dim CD16+ accompanied by a significant increase in the less mature CD56dim CD16- and CD56bright NK cell populations. Furthermore, analysis of the phosphorylation status of signalling responses in the NK cells found significant differences in pERK, pP38, pSTAT3, and pSTAT5 between the patients and healthy volunteers and remained unchanged throughout the chemotherapy. Results from this study reveals that there is a sustained decrease in the mature CD16+ NK cell sub-population frequency following long-term chemotherapy which may have clinical implications in therapeutic decision making.